Understanding of function and quadratic function among secondary school students in Selangor / Teoh Sian Hoon, Parmjit Singh and Ummi Kalsom Abdul Halim - Teoh, Sian Hoon; Singh, Parmjit; Abdul Halim, Ummi Kalsom (Penerbit UiTM (UiTM Press), 2018)
This paper highlights the importance of developing a good understanding of the topic of function. Topic of function becomes a building block for students to understand many more complex topics of mathematics. Specifically, this study aimed to investigate the relationship of students’ level of understanding between function and quadratic functions. A survey research was employed. A total of 103 samples have been involved in this study. The finding revealed that there was a strong, positive and very significant relationship of the two topics in additional mathematics among the Form Four students. It implies that the teaching and learning strategies of the two topics have to be considered simultaneously.